Evaluation of Social Forestry Programs in Community Forest Management (CFM) from the Perspective of Land Cover Change and Socio-Economic Characteristics of CFM Managers in the Protected Forest of Bukit Daun, Kepahiang Regency - Douni, James Byekher; Agustin, Deva; Akmal, Saif; Reflis, Reflis; Utama, Satria Putra (JENDELA PENGETAHUAN, 2023)
This study aims to determine changes in land cover on Community Forest Utilization Business Permits (IUPHKm) before and after the IUPHKm was issued and to determine the socio-economic characteristics of Community Forest management participants in the Bukit Daun Protected Forest at this time. Most of the community forest participants in Kepahiang Regency are still classified as less prosperous. The socio-economic conditions of community forest management participants in the Bukit Daun Protected Forest, Kepahiang Regency, show that the age of community forest permit managers in the Bukit Daun Protected Forest is in the productive age category with relatively low education. It is necessary to carry out intensive outreach activities by the Environment and Forestry Service of Bengkulu Province, UPTD KPHL Bukit Daun, regarding the primary substance and rules of the Community Forest program and implement them in the field so that the public can clearly understand the Community Forest Program.